The business of personal training - Nutting, Mark A. 1957- CSCS,*D, NSCA-CPT,*D, ACSM-HFD, ACSM-CEP, RCPT*E (Champaign, Illinois Human Kinetics, 2019)
Running a personal training business is not easy. From marketing and sales to budgets, staffing, and clientele issues, getting it right takes time-time that would probably rather spend improving your clients' fitness and wellness. That is where The Business of Personal Training comes in. Whether you are a personal trainer working for a fitness facility, an independent contractor, an independent personal trainer, or the owner of a personal training business, you will benefit from the practical guidelines, time-saving advice, and essential tools presented in this book. The Business of Personal Training will shoe you how to structure your business, plan for expenses and financing, and find the right staff. You'll learn how to market and promote the services you offer, drive referral business and customer loyalty, and expand and diversify your business. Appendixes offer business resources for additional information as well as sample templates, which are also found in the companion web resource so you can download and customize the forms as needed: nine business plan templates; seven personal trainer-client forms. There is no need to be overwhelmed. The Business of Personal Training is a comprehensive, digestible, and applicable resource that will take your business to the next level, giving you more time for what's most important
Chapter 1 Discovering your purpose and the scope of what you can do -- Chapter 2 Choosing to be a personal trainer for a fitness facility -- Chapter 3 Choosing to be a self-employed personal trainer -- Chapter 4 Choosing to be a personal trainer and facility owner -- Chapter 5 Creating a business plan -- Chapter 6 Determining your business structure -- Chapter 7 Screening and hiring your staff -- Chapter 8 Obtaining the right insurance -- Chapter 9 Determining your offerings and their pricing -- Chapter 10 Developing forms and contracts -- Chapter 11 Becoming financially profitable -- Chapter 12 marketing your services and your business -- Chapter 13 Learning the art of selling -- Chapter 14 Communicating with clients, business, and the community -- Chapter 15 Identifying options for outsourcing your tasks -- Chapter 16 Growing your business -0- Appendix A Business plan templates -- Appendix B Personal trainer-client forms -- Appendix C Business resources
Includes bibliographical references and index
Keywords: Personal trainers; Physical fitness -- Vocational guidance; Physical fitness centers -- Management -- Handbooks, manuals, etc